PERAN LITERASI KEUANGAN DAN GREEN ACCOUNTING DALAM MENINGKATKAN KINERJA KEUANGAN UMKM : THE ROLE OF FINANCIAL LITERACY AND GREEN ACCOUNTING TO ENHANCE THE FINANCIAL PERFORMANCE OF MSMEs - Badriyah, Nurul; Kamaliah, Kamaliah; Aunurrafiq, Aunnurrafiq (Universitas Riau, 2024)
This study examined the effect of green accounting and financial technology on the financial performance of Micro, Small and Medium Enterprises (MSMEs) and determine the moderating role of financial literacy on financial technology and the financial performance of MSMEs. The study sample consisted of 150 MSMEs in Siak District, Siak Regency, Riau Province. The study uses multiple linear regression and moderated regression to analyze data. The results showed that green accounting has no effect on financial performance, financial technology has an effect on financial performance and financial literacy is able to moderate the effect of financial technology on financial performance on MSMEs. These findings have implication for owner of MSMEs that MSMEs should continue the implementation of FinTech and improved their financial literacy because its improved financial performanceof MSMEs.